1998
DOI: 10.4315/0362-028x-61.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Escherichia coli O157:H7 in Salami Following Conditioning of Batter, Fermentation and Drying of Sticks, and Storage of Slices

Abstract: The fate of Escherichia coli O157:H7 was monitored in salami during conditioning of batter, fermentation and drying of sticks, and storage of slices. The raw batter (75% pork: 25% beef, wt/wt, fat content about 20%) was inoculated with a pediococcal starter culture (about 10(8) CFU/g) and a five-strain cocktail of E. coli O157:H7 ( > or = 2 x 10(7) CFU/g) and stuffed into 104-mm diameter fibrous casings. After being refrigerated at 4 degrees C or being tempered at 13 degrees C, frozen at -20 degrees C, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Conner and Kotrola (13) reported that the presence of organic acids, including acetic, citric, and lactic acids, in broth medium held at 4°C enhanced the survival of E. coli O157:H7, compared to its survival in unacidified control medium held at the same temperature. Likewise, other works have demonstrated that once induced, the acid tolerance of this pathogen is enhanced or maintained longer when the organism is held at colder temperatures (10,12,22,31,33). To determine if A cells of E. coli O157:H7 sustained acid tolerance on BCT during refrigerated storage, an additional experiment was incorporated during the course of spray wash experiments with the acid-adaptable E. coli O157:H7 strain ATCC 43889.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conner and Kotrola (13) reported that the presence of organic acids, including acetic, citric, and lactic acids, in broth medium held at 4°C enhanced the survival of E. coli O157:H7, compared to its survival in unacidified control medium held at the same temperature. Likewise, other works have demonstrated that once induced, the acid tolerance of this pathogen is enhanced or maintained longer when the organism is held at colder temperatures (10,12,22,31,33). To determine if A cells of E. coli O157:H7 sustained acid tolerance on BCT during refrigerated storage, an additional experiment was incorporated during the course of spray wash experiments with the acid-adaptable E. coli O157:H7 strain ATCC 43889.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to promoting survival in low-pH foods, the development of acid resistance by E. coli O157:H7 may provide cross-protection against heat, salt, and irradiation preservation of foods (7,11,23,36). Furthermore, several works have indicated that acid tolerance of E. coli O157:H7 is enhanced or sustained longer upon refrigerated storage (10,12,22,31,33). Finally, it is thought that acid resistance and/or induction of acid tolerance may better enable pathogens to survive gastrointestinal acidity and ultimately cause disease and that it may enhance virulence (1,15,26,35).…”
mentioning
confidence: 99%
“…Freezing of raw meat prior to be used in DFS production is not uncommon. Bacteria in the meat can be damaged by a freeze/thaw process, and this has been shown to provide an extra 0.5-1-log reduction of E. coli O157:H7 in the final salami product [213]. Another strategy, commercially used in the USA, is heat treatments of raw meat ingredients by lactic acid-hot water (80-90 ∘ C).…”
Section: Reductions Of Pathogens In Raw Meatmentioning
confidence: 99%
“…However, pathogenic Escherichia coli can contaminate and survive in fermented meat products at levels sufficient to cause serious illness in consumers, as evidenced by numerous outbreaks of E. coli infections epidemiologically linked to uncooked fermented meat products (8,9,54,64). Knowledge of the kinetics of nonthermal inactivation of E. coli, and the factors affecting it, is important to be able to optimize the safety of fermented meat processes.Several research groups have conducted studies on the survival of pathogenic E. coli during the processing of specific fermented meat products (4,6,14,16,23,25). In some cases, the effects of alternative ingredients or processing parameters have also been determined (12,21,24,30).…”
mentioning
confidence: 99%
“…Several research groups have conducted studies on the survival of pathogenic E. coli during the processing of specific fermented meat products (4,6,14,16,23,25). In some cases, the effects of alternative ingredients or processing parameters have also been determined (12,21,24,30).…”
mentioning
confidence: 99%